2020
DOI: 10.1002/bimj.201900163
|View full text |Cite
|
Sign up to set email alerts
|

False discovery rate control for multiple testing based on discretep‐values

Abstract: For multiple testing based on discrete p‐values, we propose a false discovery rate (FDR) procedure “BH+” with proven conservativeness. BH+ is at least as powerful as the BH (i.e., Benjamini‐Hochberg) procedure when they are applied to superuniform p‐values. Further, when applied to mid‐p‐values, BH+ can be more powerful than it is applied to conventional p‐values. An easily verifiable necessary and sufficient condition for this is provided. BH+ is perhaps the first conservative FDR procedure applicable to mid‐… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Further, in our simulation studies, we have observed considerable power improvement of the wFDR procedure over the procedures of Habiger (2015), Döhler et al. (2018), and Chen (2019). However, it is challenging to derive simple, analytic conditions for which the wFDR procedure has no less rejections than these three procedures because the former uses discrete p ‐values and the latter three use randomized p ‐values, a complicated step‐up critical sequence, or mid p ‐values, respectively.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Further, in our simulation studies, we have observed considerable power improvement of the wFDR procedure over the procedures of Habiger (2015), Döhler et al. (2018), and Chen (2019). However, it is challenging to derive simple, analytic conditions for which the wFDR procedure has no less rejections than these three procedures because the former uses discrete p ‐values and the latter three use randomized p ‐values, a complicated step‐up critical sequence, or mid p ‐values, respectively.…”
Section: Discussionsupporting
confidence: 49%
“…(2018), the procedure (BHH) of Heyse (2011), the randomized Storey procedure (SR) of Habiger (2015) (with tuning parameter λ=0.5 because other methods such as “smoother” and “bootstrap” provided by the sans-serifqvalue package to determine λ seems to make the resulting SR a bit anticonservative in the simulation studies to be presented next), the “aHSU” procedure of Döhler et al. (2018), and the “BH+” procedure of Chen (2019). The BH+ procedure is proven by Chen (2019) to be conservative and will be applied to two‐sided mid‐ p ‐values and be denoted by “BH+MidP”; a definition of mid‐ p ‐value can be found in Hwang and Yang (2001).…”
Section: Simulation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the adjusted discrete p ‐values of Heller and Gur (2012) and Heyse (2011) reduce to the ones for continuous p ‐values in Benjamini and Hochberg (1995) and Benjamini and Yekutieli (2001), respectively, when applied to hdu p ‐values, leaving the results unchanged. The same holds true for the method of Chen (2020). Therefore, we decide to focus our research on the q ‐value approach proposed by Storey (2003) but based on estimators of the proportion of true null hypotheses, π0, which take the discreteness of the p ‐values into account.…”
Section: Introductionsupporting
confidence: 53%
“…More precisely, they proved the FDR control of the BH procedure applied to two‐sided mid p ‐values of Binomial tests and Fisher's exact tests. In the same line of research, Chen (2020) proposed a new BH procedure which controls the FDR when applied to mid‐ p ‐values and to p ‐values with general distributions.…”
Section: Introductionmentioning
confidence: 99%